TRANSITION TO ONLINE EDUCATION: RESEARCH OF VIDEO TEACHING CHALLENGES DURING COVID 19 PANDEMIC - Miseviciene, Regina; Rimavicius, Vidmantas; Makackas, Dalius (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Since 2020 middle of March many universities transposed the study process to online environment. Kaunas University of Technology within two weeks completely transferred the study process to the online space also. The following tools Zoom, Big Blue Button, Adobe Connect, MS Teams, Loom, Web Meetings have been offered for working remotely.To reveal the learners' experience and evaluate the above-mentioned video conferencing technologies in the education process, the authors of this article conducted a case study involving 354 second-year students of the Faculty of Informatics. The case study was accomplished in June 2020, after the end of quarantine in our country.The aim of the work was to reveal the learners' experience and summarize the results using different types of video conferencing systems.The case study showed that the rapid transition to online form of education has been quite successful and that lessons learned can be used in the future in circumstances like COVID 19.